Green building theory and regression experiment analysis based on the sustainable development of green environment. (4th February 2021) - Yu, Chunlin; Fang, Xi
Cities are areas with highly dense buildings, and are also important places for energy consumption and waste generation. Therefore, the development of buildings with low energy consumption and low pollutant emissions is an important way for cities in my country to achieve energy conservation, emission reduction and sustainable development. The concept and practice of green building came into being in this context. Based on the analysis of the research results of green buildings and sustainable environmental green technologies, this paper uses multiple regression experiments combined with the development differences of green buildings in nearly 300 cities in China to analyse economic, policy, technical and other factors.